THE INFLUENCE OF WORKING CAPITAL MANAGEMENT AND SALES GROWTH ON PROFITABILITY AT PT. PANJI ANUGERAH SENTOSA MEDAN IN 2022-2024 - Alya Azizah; Toni Hidayat; Wan Dian Safina; Muhammad Rahmat (PT. Radja Intercontinental Publishing, 2025)
This study aims to analyze and gain a deep understanding of the effect of working capital management and sales growth on profitability at PT. Panji Anugerah Sentosa Medan during the period 2022 to 2024. The population in this study consists of the company's annual financial statements, including the balance sheet and income statement for that period. The sampling technique used is total sampling, where all available data is used as a research sample. The approach used in this study is quantitative, utilizing primary and secondary data obtained from the company's annual financial statements. To analyze the data, a multivariate analysis method was applied using multiple linear regression. The results of the analysis show that based on the partial t-test, the working capital management variable has a significance value of 0.00 and a regression coefficient of 4.718. This indicates that working capital management has a positive and significant effect on the company's profitability as measured by the Return On Asset (ROA) ratio. Meanwhile, the sales growth variable shows a significance value of 0.137 and a regression coefficient of -1.526, which indicates that sales growth does not have a significant effect on the company's profitability based on the ROA ratio.